COMPRESSIVE STRENGTH AND HYDRATION PROPERTY OF HIGH-STRENGTH MORTAR USING VARIOUS CEMENT - TAKAHASHI, Keita; MARUYA, Eiji; TAKAHASHI, Toshiyuki (Cement Science and Concrete Technology, 2013)
Recently, Ultra High strength fiber reinforced concrete（UFC）has been developed which has high compressive strength, toughness and also durability. However the usual UFC is cured under high temperature, so it is now expected to develop the new UFC which could place on field. There are two subjects to figure out developing the new UFC, obtaining the high hydration reactivity of binder on early stage under ordinary temperature to place the UFC on field and reducing the water-binder ratio getting the high strength. Accordingly it is important to find out the proper combination of these two for new UFC. In this study, we prepare the three type of cement（No.1 is high C3S-low C3A, No.2 is high C3S-high C3A and No.3 is high C2S.）and three water-binder ratio（14％, 16％, 18％）, the binder includes cement and pozzolan. Then we examine mortar flow, compressive strength and hydration property（Reaction rate of C3S and pozzolan, bound water of CSH, AFm and CH, and porosity）. As a result, obtaining high compressive strength on early stage under ordinary temperature, it is essential that a cement contains low C3A and high C3S and a mortar has excellent fluidity. This type of cement could have a relatively large number of free water, so the reaction of C3S and pozzolan tend to occur at the level of low binder-water ratio.